PENGARUH CUSTOMER PERCEIVED VALUE TERHADAP CUSTOMER LOYALTY MELALUI CUSTOMER SATISFACTION PADA 3SECOND ROYAL PLAZA SURABAYA. - Tanujaya, Andrea (JURNAL ILMIAH MAHASISWA MANAJEMEN, 2012)
The rise of shopping centers and modern luxury in the city of Surabaya, especially which was built by the private sector raises worries and concern of traditional merchants. In order to get customer loyalty, so the Factory outlets are trying to identify the various points of view of consumers. One of the Factory Outlet that could be an attraction is 3Second Royal Plaza Surabaya. Therefore, the purpose of this study was to determine the influence of Customer Perceived Value on Customer Loyalty with mediation of Customer Satisfaction at 3Second Royal Plaza Surabaya. Design of this study is using survey method of the 150 respondents with the analysis technique used in this study was the Structural Equation Modeling (SEM) with the help of the program LISREL 8.8. Respondents were taken from some consumers who are in Royal Plaza and consumers that had shopped at 3second in Surabaya. The results showed that: (1) there is the influence of Customer Perceived Value to Customer Satisfaction; (2) there is the influence of Customer Perceived Value to Customer Loyalty; (3) there is the influence of Customer Satisfaction to Customer Loyalty; and (4) there is the influence of Customer Perceived Value to Customer Loyalty mediated by Customer Satisfaction.